The choroid plexus response to a repeated peripheral inflammatory stimulus - Marques, Fernanda (2009)
BACKGROUND: Chronic systemic inflammation triggers alterations in the central nervous system that may relate to the underlying inflammatory component reported in neurodegenerative disorders such as multiple sclerosis and Alzheimer's disease. However, it is far from being understood whether and how peripheral inflammation contributes to induce brain inflammatory response in such illnesses. As part of the barriers that separate the blood from the brain, the choroid plexus conveys inflammatory immune signals into the brain, largely through alterations in the composition of the cerebrospinal fluid. RESULTS: In the present study we investigated the mouse choroid plexus gene expression profile, using microarray analyses, in response to a repeated inflammatory stimulus induced by the intraperitoneal administration of lipopolysaccharide every two weeks for a period of three months; mice were sacrificed 3 and 15 days after the last lipopolysaccharide injection. The data show that the choroid plexus displays a sustained response to the repeated inflammatory stimuli by altering the expression profile of several genes. From a total of 24,000 probes, 369 are up-regulated and 167 are down-regulated 3 days after the last lipopolysaccharide injection, while at 15 days the number decreases to 98 and 128, respectively. The pathways displaying the most significant changes include those facilitating entry of cells into the cerebrospinal fluid, and those participating in the innate immune response to infection. CONCLUSION: These observations contribute to a better understanding of the brain response to peripheral inflammation and pave the way to study their impact on the progression of several disorders of the central nervous system in which inflammation is known to be implicated.